IMPLEMENTATION OF IN-GROUP COUNSELING CAREER CHOICE COACHING IN MAN 1 MEDAN STUDENTS: IMPLEMENTASI KONSELING KELOMPOK DALAM PEMBINAAN PEMILIHAN KARIR PADA SISWA MAN 1 MEDAN - Cahyadi Nasution, Muhammad (LPPM UPMI, 2023)
The regional government system is closely related to regional autonomy which is currently taking place in Indonesia. Before regional autonomy was introduced, all government systems were centralized or centralized. With the implementation of regional autonomy, it is hoped that regions will be able to regulate their own government systems by maximizing their regional potential. However, some things are still controlled by the central government. Such as diplomatic relations, trade cooperation. In accordance with the mandate of the 1945 Constitution, Regional Governments have the authority to regulate and manage government affairs themselves according to the principles of autonomy and assistance duties. The granting of broad autonomy to regions is directed at accelerating the realization of community welfare through improving services, empowerment and community participation. Apart from that, through broad autonomy, regions are expected to be able to increase their competitiveness by paying attention to the principles of democracy, equality, justice, privileges and specialties as well as regional potential and diversity in the system of the Unitary State of the Republic of Indonesia. In order to be able to carry out this role, regions are given the broadest possible authority accompanied by the granting of rights and obligations to carry out regional autonomy within the unity of the state government administration system. Meanwhile, regional government is also a training ground and development of democracy in a country. Whether we realize it or not, the regional government system is actually preparation for the advanced political career that usually occurs in central government. However, along with changes in the law regarding regional government, the authority for regional administration also differs from each of these changes.